2003
DOI: 10.1002/ldr.571
|View full text |Cite
|
Sign up to set email alerts
|

Water, land and health in urban and peri‐urban food production: the case of Kano, Nigeria

Abstract: In sub-Saharan Africa, urban and peri-urban food production has been identified as an important resource for meeting the challenges of rapidly growing cities, and the positive aspects of such production have been well documented in the literature. This paper examines some of the health and environmental concerns associated with urban and peri-urban agriculture (UPA). Empirical evidence from the city of Kano in northern Nigeria suggests that there is currently much reason for concern as industrial and domestic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 17 publications
(9 reference statements)
2
69
0
1
Order By: Relevance
“…Figure 1 shows seasonal variations; in which dry season had relatively higher heavy metals concentrations than the wet season, although not statistically significant at P≤0.05. This variation could be due to higher evapotranspiration that occurred in the dry season without other input into the drainage basin through rainfall (Bichi, 2000;Binns et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows seasonal variations; in which dry season had relatively higher heavy metals concentrations than the wet season, although not statistically significant at P≤0.05. This variation could be due to higher evapotranspiration that occurred in the dry season without other input into the drainage basin through rainfall (Bichi, 2000;Binns et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…All of these especially the tanneries and textile industries, use largest quantities of water and producing the greatest amounts of wastewater, that constitute the main sources of point pollution. A 1989 study, which monitored the activities of 15 tanneries in Kano, found that in all cases permissible limits for effluents discharge were violated (Binns et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the surrounding towns become strategic zones for the expansion of urban areas. Prior studies by Binns,Maconachie & Tanko (2003) and Lawanson, Yadua, & Salako (2012) have shown that Lagos as a rapidly urbanising region is not exempted from this phenomenon. The major push and pull factors influencing urban-rural residential mobility are land affordability, improved road network and provision of gated exclusive housing developments by private developers in the peri-urban thus creating metropolitanisation of the study areas.…”
Section: Resultsmentioning
confidence: 97%
“…Notable investigation were on rural-urban linkages, environmental quality and livelihoods in Nigerian peri-urban settlements (Bah, Diyamett, Lerise, Okali &Tacoli, 2003;Binns, Maconachie, & Tanko, 2003;Nwokoro & Dekolo, 2012;Lawanson, Yadua, & Salako, 2012). Therefore, this study seeks to examine the differentials in metropolitanisation of Lagos peri-urban settlements by specifically assessing the causes, extent, actors and policy implication of the peri-urbanisation process in Lagos metropolitan peripheral.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, for instance, farmers relied mainly on physical indicators such as color, odor, and debris on water to ascertain the level of contamination in water and the related risk. In Kano, Nigeria, some of the farmers using untreated industrial effluents from breweries and tanneries used color, smell, and the formation of foam to determine unfavorable and undesirable conditions (Binns, Maconachie, & Tanko, 2003). Knudsen et al (2008) similarly illustrated how farmers in peri-urban Hanoi, Vietnam, use locally adapted indicators to characterize wastewater.…”
Section: Enabling Actors To Visualize the Invisiblementioning
confidence: 99%